Ruminations on the « Benefit » Package - Schultz, L. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1973)
The author reviews the evidence to see if there is general agreement on the definition of fringe benefits and examines the difficulties encountered in Computing the benefits.